E-Government, the Era of Disruption and the Future of Public Service in Indonesia - Muhammad Musaad (Universitas Dharma Wacana, 2022)
In the age of disruption, information and communication technology (ICT) is critical to the development of a company and the people who use it. In this day and age of disruption, the government promotes ministries and institutions to transition from manual to electronic information delivery, often known as E-Government. The whole public has access to it. The use of e-government is intended to boost public service transactions that are not restricted by time or place, and at a low cost to the community. The purpose of this research is to investigate E-Government, the age of disruption, as the future of government services in Indonesia. A qualitative investigation using a descriptive method is used in this study. The study's findings show that implementing e-government brings benefits from the economic, social, and government dimensions, as well as the perspective of public services, such as cost savings, economic development support, increased transparency, better services for the community, and participation in community empowerment. Meanwhile, in this disruptive age, the deployment of E-Government in public services via the use of Information and Communication Technology by government entities and institutions reflects this. According to the findings of this study, the performance of E-Government in public services in Indonesia is now beginning to grow in quantity. Still, in the future, it must be able to produce high-quality goods in order to keep up with other nations across the globe